2012
DOI: 10.1111/j.1751-553x.2012.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of VKORC1 (C1173T) and CYP2C9 genetic polymorphisms in Egyptians and their influence on warfarin maintenance dose: proposal for a new dosing regimen

Abstract: VKORC1-TT and CYP2C9 *1/*1 are the most prevalent genotypes among Egyptians. Patients with VKORC1-TT genotype required a lower warfarin dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
8
11
0
Order By: Relevance
“…This variability in dose requirement could be attributed to the fact that CYP2C9*1 metabolizes warfarin normally, CYP2C9*2 reduces warfarin metabolism by 66%, and CYP2C9*3 reduces warfarin metabolism by 95%. These data are in agreement with those reported by previous studies conducted in Egyptian population [17,18,20].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This variability in dose requirement could be attributed to the fact that CYP2C9*1 metabolizes warfarin normally, CYP2C9*2 reduces warfarin metabolism by 66%, and CYP2C9*3 reduces warfarin metabolism by 95%. These data are in agreement with those reported by previous studies conducted in Egyptian population [17,18,20].…”
Section: Discussionsupporting
confidence: 93%
“…This variability in dose requirement could be attributed to the fact that carriers of the A allele haplotype (i.e., -1639 A) produce less VKORC1 than carriers of B allele haplotype (i.e., -1639 G) [19]. These data are in agreement with those reported by previous studies conducted in Egyptian population [17,18,20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They reported that it might be possible that this was because of the minimal variation in height, which varied in the population by less than 4 %. Furthermore, El Din et al [27] reported that bodyweight showed no influence on dose variability. Moreover, the target INR in our study was 2-3.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there were no warfarin pharmacogenomic studies carried in Egypt, with the exception of only three studies [26,27,30] in the preceding 2 years. The novel attribute of our study was the development of a warfarin dosing algorithm based on the genetic and nongenetic factors of the study cohort, and the validation of the calculated warfarin dosing algorithm in a different cohort with a significant positive correlation observed between the predicted warfarin dose and the actual prescribed dose.…”
Section: Discussionmentioning
confidence: 99%